How Does Hotel Service Innovation Affect Experiential Value and Consumer Decisions to Stay in Hotels? - Wahyu Eko Setianingsih; Nursaidah Nursaidah (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This research is intended to examine how hotel service innovation affects consumer decisions to stay at hotels with the intervening variable of experiential value.Design/Methodology/Approach: This explanatory research was intended to explain the effect of exogenous variables on endogenous variables by involving an intervening variable. The subjects of this research were consumers of 3-star hotels in Jember City, East Java. The research population was consumers who used hotel services in Jember City, and the sample was determined by accidental sampling. The number of samples was 90 respondents. Data analysis was then carried out by Structural Equation Model Partial Least Square (SEM-PLS) with the assistance of Smart PLS 4 software.Research findings: The results prove that hotel service innovation positively affected the experiential value and consumer decisions. In addition, it was found that there was an indirect effect of hotel service innovation on consumer decisions through intervening experiential value.Theoretical contribution/Originality: The research examined the model's use of experiential value to intervene in the relationship between hotel service innovation and consumer decisions and better explain consumer behavior. The research also gives contribution to the development of marketing management literature.Practitioner/Policy implication: The results of this study can be considered in hotel marketing, where the impact of the COVID-19 pandemic requires marketing strategies, including service innovation.Research limitations/Implications: This research was only conducted on hotel consumers in the scope of Jember City, so it is necessary to conduct research in a broader area in the future. Future research must also examine service innovation and its effect on customer satisfaction and loyalty.